Transforming the Authority of the Archive : Undergraduate Pedagogy and Critical Digital Archives - Gustavson, Andi; Nunes, Charlotte; Project Muse. (Ann Arbor : Lever Press, 2023)
"This edited collection addresses the proliferation in recent years of community-engaged archives projects in the context of higher education. Featuring perspectives from educators, archivists (both community- and institutionally-affiliated), and undergraduates involved in efforts to deconstruct and transform the institutional authority of the archive, the volume details new roles for archives in undergraduate pedagogy and new roles for undergraduates in archives. While there has long been a place for archival exploration in undergraduate education, especially primary source analysis of items curated by archivists and educators, the models offered here engage students not only in analyzing collections, but also in the manifold challenges of building, stewarding, and communicating about collections. In transforming what archives are to undergraduate education, such projects as are profiled here transform the authority of the archive, as students and community partners claim powers to curate and create history. The volume is informed and inspired by recent scholarship in critical digital archives, Critical Archival Studies at large, and community-based archives. Contributions to this volume represent a wide range of institutions, from small liberal arts colleges to HBCUs to Ivy Leagues to large research institutions. Not all the projects detailed in this collection are primarily affiliated with academic institutions. Chapters focused on community- rather than campus-based archives projects address how they have involved significant undergraduate labor and leadership, and offer insight into the interaction between community archives and academic institutions.The assignments, projects, and initiatives described across this collection are fundamentally concerned with the challenge to model digital archival collections so as to center individual and community voices that are historically under-engaged in the archives. To address this challenge, contributors describe various approaches to substantively, often radically, redistribute archival resources and authority"--
Description based on print version record.
Keywords: Electronic books